Nghiên cứu tình hình nhiễm khuẩn vết mổ tại một số khoa ngoại, Bệnh viện Trung ương Huế - Hùng, Nguyễn Việt; Luyện, Trần Hữu; Phồn, Đặng Như; Phương, Trần Thị Thủy; Bình, Lê Văn; Tú, Nguyễn Thị Thanh; Hằng, Phạm Vũ Thúy; Nga, Phan Thị; Diệu, Thân Thị; Hòa, Nguyễn Thị Mai; và c.s. (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.